2022
DOI: 10.3390/pr10020389
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Synthesis of Silver Nanoparticles from Waste Agricultural Biomass and Its Antimicrobial Activity

Abstract: The problem of cleaning and disinfecting surfaces has become extremely important in the context of the ongoing SARS-CoV-2 coronavirus pandemic. However, it should be considered that, in everyday life, we come into contact with many other viruses, as well as pathogenic bacteria and fungi, that may cause infections and diseases. Hence, there is a continuous need to search for new and more effective methods of fighting pathogens. Due to their documented antimicrobial activity, silver nanoparticles may be an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…According to Marín et al [68], the antimicrobial properties of natural matrices are usually associated with the presence of dietary polyphenols that are metabolized by gut microbiota into simple bioactive compounds with diverse effects. The studies of Wolny-Koładka et al [74] and Roy et al [75] also suggested using the waste from parsley leaves or stems to produce silver nanoparticles with significant antimicrobial effects against Klebsiella pneumonia, S. aureus and Escherichia coli.…”
Section: Resultsmentioning
confidence: 99%
“…According to Marín et al [68], the antimicrobial properties of natural matrices are usually associated with the presence of dietary polyphenols that are metabolized by gut microbiota into simple bioactive compounds with diverse effects. The studies of Wolny-Koładka et al [74] and Roy et al [75] also suggested using the waste from parsley leaves or stems to produce silver nanoparticles with significant antimicrobial effects against Klebsiella pneumonia, S. aureus and Escherichia coli.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the attainment of silver nanoparticles depends on numerous factors, such as the genetic properties of the organisms or the environmental conditions [11]. If sintering silver through this process, we could consider it a biobased material [25]. Even so, silver is a problem for submarine life and is not biodegradable, becoming a problem for the environment [18].…”
Section: Conductive Inksmentioning
confidence: 99%
“…This technique involves production of NPs using biological resources, which effectively overcomes the drawbacks imposed by physical and chemical methods [29]. A few examples include Cu NPs from seeds of Illicium vercium (star anise) and Mysristica fragrans (nutmeg) [30], Ag NPs from agricultural wastes [31] and extracts of red currant and bilberry wastes [32]. Being eco-friendly, this approach does not require the involvement of noxious chemicals and extreme conditions.…”
Section: Green Synthesis Of Nanoparticlesmentioning
confidence: 99%